The Role of Grammar Instruction in Developing Communicative Proficiency: What the Secondary Level Teachers say - Bhatt, Prithvi Raj (Journal of NELTA, 2020)
Grammar instruction plays a pivotal role in an EFL context but the way grammar is taught depends upon the availability of teaching materials and resources, students’ expectations, teachers’ maxims and beliefs, and the organizational culture of schools. The present article is an attempt to find out secondary teachers’ views regarding the role of grammar instruction to develop communicative proficiency. The study also aimed at finding out what attempts they make for balanced language development (i.e., accuracy, fluency and restructuring). The study used purposive sampling and semi-structured interviews to generate data. After thematically and descriptively interpreting the data, the study found that teachers are positive towards the role of grammar instruction in EFL to develop communicative proficiency of the learners. The study also found that grammar error correction prevents learners from the risk of fossilisation. Furthermore, the teachers emphasised both accuracy and fluency for the organic development of English in learners’ minds and were aware of the use of various teaching of grammar resources for effective teaching. Finally, the article draws pedagogic and research implications for English language teachers.